On the anxiety concerning of imminent prospect of the microchipping of employees: Remarks in the context of the emerging legislation in the USA - Surdykowska, Barbara (Z Problematyki Prawa Pracy i Polityki Socjalnej, 2023)
Barbara Surdykowska draws attention to legislation, specifically in the US, which prohibits (or emphasizes the importance of the employee’s consent to) subcutaneous microchipping in the context of work relations. In Surdykowska’s opinion, issue of the use of microchips in the labor context and the potential decisions of the legislator may serve as a litmus test of reactions to the expected technological transformation. The simultaneous and progressive use of subcutaneous microchips is at this point a very early phase of the phenomenon of the cyborgization of the employee’s body.